Eudendrium album Nutting 1896 - Calder, Dale R. (Zenodo, 2012)
Eudendrium album Nutting, 1896 Figs. 1, 2 Eudendrium album Nutting, 1896: 146. Type locality. UK: Plymouth, Millbay Channel, on stones in shallow water (Nutting 1896: 146). Museum material. Kosterhavet, 58°53.030’N, 11°05.567’E, 140– 100 m, 10.ix.2010, biological dredge, R / V Nereus , one straggly colony with pedicels up to c. 10 mm high, without gonophores, ROMIZ B3919.— Kosterhavet, 58°53.367’N, 11°04.240’E, 90 m, 15.ix.2010, biological dredge, R / V Nereus , one sparingly branched colony, up to 8 mm high, on a polychaete tube, without gonophores, ROMIZ B3934. Remarks. Schuchert (2008b) included 19 species, excluding the problematic Myrionema multicornis (Allman, 1876), in his review of eudendriids from Europe. These were differentiated largely on the basis of nematocyst complement. Two small species of the genus Eudendrium Ehrenberg, 1834 were distinguished from others in having macrobasic euryteles scattered over the hydranth body. Thread coils of these nematocysts are oblique to the capsule axis in Eudendrium album Nutting, 1896 and parallel in E. simplex Pieper, 1884. The two also differ in gonophore type, with those of E. album being gonochoristic and those of E. simplex being hermaphroditic. Eudendrium simplex is known only from the Mediterranean, where it occurs on the sea grass Posidonia , while Eudendrium album is a typically boreal species extending northwards to Scandinavia and Iceland (Schuchert 2008b). Eudendrium album is reported here for the first time from the west coast of Sweden. The identification is based largely on its cnidome, comprising small heterotrichous microbasic euryteles and macrobasic euryteles (Figs. 2a– c). These are much as described in Schuchert’s (2008b) account of the species. Eudendrium capillare Alder, 1856, reported from the study area (Segerstedt 1889; Jäderholm 1909; Kramp 1935b; Jägerskiöld 1971), from Denmark (Kramp 1935b), and from the Oslofjord (Christiansen 1972), is similar but lacks macrobasic euryteles. For discussion of Myrionema multicornis , see Schuchert ...